How reacted USA with the first case of bubonic plague on 21 August? - Chire Saire, Josimar E. (2022)
The present work studies the reactions of citizens from United States of America (USA) during the first cases of Bubonic Plague in the territory on August 2020, during pandemic generated by Covid-19. The interest of the study is analyze the posts of users from all the states of USA following a Text Mining approach. The collection of data is performed through Twitter Application Program Interface (API) of Twitter, considering keywords: bubonic plague and black death. The results show that the states with highest number of coronavirus have more publication than others and the interests are around treatments, political issues and public health.